Facile preparation and characterization of temperature-responsive hydrophilic crosslinked polymer microspheres by aqueous dispersion polymerization. (5th April 2020) - Du, Wenhao; Wu, Pengwei; Zhao, Zhixin; Zhang, Xi
Graphical abstract: Highlights: Crosslinked microspheres can be prepared by eco-friendly aqueous dispersion polymerization. Chain transfer reaction of crosslinker can be used to achieve the crosslinking. Zwitterionic interaction can be utilized to provide temperature-responsive property. The microspheres can be reused due to their deformability. The influence law of process conditions on diameter of microspheres can be obtained in this paper. Abstract: Aqueous dispersion polymerization is an environmentally friendly and low-energy method for the preparation of micron polymer microspheres. Crosslinked polymer microspheres could be obtained by aqueous dispersion polymerization via methods such as controlled radical polymerization. However, most of these commonly used cross-linking methods are complicated and the product is toxic. Herein, we provided a facile approach for the preparation of temperature-responsive crosslinked polymer microspheres (c-PMAD) by aqueous dispersion polymerization. Chain transfer reaction of 2-(dimethylamino) ethyl methacrylate (DMAEMA) instead of traditional crosslinkers was used to achieve the crosslinking. It is found that the microsphere is a spherical material with uniform surface, which has an average particle size of 5.21 μm in deionized water at 25 °C. It has a relatively high thermal stability. The microsphere has the upper critical solution temperature transition (UCST) behavior at 66.5 °C. The particle size of c-PMAD could increase with increasing temperature and decrease with increasing dosage of NaCl. Moreover, diameter of c-PMAD could decrease to original size with decreasing temperature, which endows it the feature of reusing. The UCST behavior of c-PMAD could be kept in 8 wt% NaCl solution. In addition, the effect of process conditions of preparation on the particle size of microspheres were studied in this paper. Micron-sized microspheres could be obtained at 45–65 °C. Microspheres size decreased with increasing initiator dosage, decreasing monomers concentration, increasing of acrylamide dosage and increasing of crosslinker dosage.